Análise das condições do pavimento asfáltico em áreas urbanas - estudo de caso: rua Antonio Gurjão/ bairro São Geraldo – Pau Dos Ferros –RN - Almeida Neto, Alfredo Torres de (Universidade Federal Rural do Semi-Árido, 2019)
The road transport system, the most used modality in Brazil, is going through great problems the bad conditions of the pavements. Without periodic conservation or month of the deepest restorations, users coexist with the difficulty of carrying out their travels, due to poor rolling conditions, increasing travel time, increased costs with fuel consumption and maintenance of vehicles and with the occurrence of accidents, among other damages. However, the lack of maintenance of the road infrastructure is reflected in cities whose road system is unsafe, without safety and comfort, in addition to negligence with signaling, interfering with the mobility and accessibility of users, whether drivers of vehicles, motorized or not, whether pedestrian . Therefore, the study, quality control of the raw material, the execution and conservation of pavement quality are of relevant importance, in order to maintain good traffic conditions, guaranteeing comfort and safety to drivers. The importance of drainage equipment for good pavement durability, both in rural and urban roads, is also highlighted. This study analyzes the conditions of asphalt pavement in urban areas, specifically the Antônio Gurjão street stretch in the city of Pau dos Ferros - RN, verifying causes and making suggestions for improvement. For this purpose, a volumetric counting survey was carried out to determine the quantity, direction and composition of traffic flow in the site, photographically recording the problems caused by the conditions and bearing and the lack of drainage of the pavement water. The results pointed to the advanced state of deterioration of the pavement and absence of drainage elements at the site. The following alternative solutions were suggested: the construction of lateral gutters for drainage of rainwater, implementation of the sanitary drainage system and for the recovery of the pavement; removal of the existing asphalt material through the milling process; the regularization of the base with compaction and subsequent execution of a new asphalt layer.
Keywords: Pavimento; Drenagem; Durabilidade; Patologia; Flooring; Drainage; Durability; Pathology; ENGENHARIAS::ENGENHARIA CIVIL